Characterization of symptoms and growth in Italian Pumpkin (Cucurbita pepo L.) under micronutrient lack (Research, Society and Development, 2020)
Vegetables need nutrients to maintain their life, due to the functions that these elements perform. This study aimed to evaluate the typical symptoms of nutritional deficiency in zucchini related to micronutrients, through visual diagnosis and growth. The statistical design used was the totally random with three replications, containing 6 treatments, in nutrient solution. The treatments were: complete nutrient solution (control), nutrient solutions with individual omissions of B, Cu, Fe, Mn and Zn. After germination, the seedlings were transferred to the complete nutrient solution with 10% of their ionic strength (adaptation period), which remained under constant aeration and then transplanted to plastic vessels (8L) with nutrient solution. The observed symptoms were photographed and described. After the manifestation of visual deficiency symptoms, the treatments were collected. At fifteen days, boron-omitting plants began to show reduced growth. Through the parameters of growth and dry matter production evaluated, it was observed that the omissions provided significant differences in the plants of Zucchini. Under severe omission, the thrown leaves were malformed, smaller and thicker, and even death of the growth points. The omission of nutrients B and Fe in nutrient solution can be translated into characteristic deficiency symptoms of each nutrient. The omission of micronutrients affects that of Zucchini. The omission of micronutrients that most limit the different parts to plants is Fe and B.